PERLINDUNGAN HUKUM TERHADAP MOTIF TATO SUKU DAYAK IBAN DI KALIMANTAN BARAT DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 28 TAHUN 2014 - NIM. A1011201215, MARIANA THERENSIA VIOLETHA (Jurnal Fatwa Hukum, 2024)
Abstract                       Iban Dayak Tribal Tattoos are works of art with tattoo motifs created by the Iban people and have a philosophy that is considered a Traditional Cultural Expression, according to Law no. 28 of 2014 (UUHC), Copyright is an exclusive right that arises automatically. The aim of this research is to examine the history and meaning of Dayak Iban tribal tattoo motifs and analyze government actions in protecting, preserving and introducing Dayak Iban tribal tattoo motifs. The research method used is an empirical method with primary data, namely direct interviews with Iban Dayak traditional leaders, Iban Dayak tattoo artists, and people whose body parts have Iban tattoo motifs. The sampling technique in this research is a Saturated Sampling technique where the sample selection is taken from all members of the population. The data collected is then explained qualitatively and presented deductively.From the research results, it can be seen that Dayak Iban tribal tattoos have received automatic legal protection as stipulated in Law no. 28 of 2014 Copyright, aspects of protection are also provided through recognition of Traditional Cultural Heritage (EBT). The government has carried out an inventory of EBT, but its implementation is still not optimal. Cultural asset stakeholders and activists have carried out their responsibilities in maintaining, preserving and introducing Dayak Iban tribal tattoo motifs in various forms.        Keywords: Dayak Iban Tribal Tattoo Motifs, Effectiveness Legal Protection, Traditional Cultural Expression (EBT).  Abstrak Tato Suku Dayak Iban merupakan karya seni motif tato yang diciptakan oleh masyarakat Iban serta memiliki filosofi sehingga masuk sebagai Ekspresi Budaya Tradisional, menurut   Undang-Undang No. 28 Tahun 2014 (UUHC), Hak Cipta adalah hak eksklusif yang timbul secara otomatis. Tujuan penelitian ini untuk mengkaji sejarah dan makna dari motif tato suku dayak iban serta menganalisis tindakan pemerintah dalam menjaga, melestarikan, dan memperkenalkan motif tato suku Dayak Iban. Metode penelitian yang digunakan adalah metode empiris dengan data primernya yaitu wawancara langsung kepada tokoh adat dayak Iban, seniman tato dayak Iban, dan masyarakat yang bagian tubuhnya memiliki motif tato iban. Teknik pengambilan sampel dalam penelitian ini merupakan teknik Sampling Jenuh dimana pemilihan sampel diambil dari jumlah semua anggota populasi. Data yang didapat kemudian dianalisis secara kualitatif dan disajikan secara deduktif.Dari hasil penelitian dapat diketahui bahwa tato suku dayak iban   sudah mendapat perlindungan hukum secara otomatis sebagaimana ditentukan dalam Undang-Undang No. 28 Tahun 2014 Hak Cipta, aspek perlindungan juga diberikan melalui pengakuan Warisan Budaya Tradisional (EBT). Pemerintah sudah melakukan inventarisasi terhadap EBT, namun pada pelaksanaannya masih belum optimal. pemangku dan para pegiat aset budaya telah melakukan tanggung jawab dalam menjaga, melestarikan dan memperkenalkan motif tato suku dayak iban dalam berbagai bentuk.  Kata Kunci: Ekspresi Budaya Tradisional(EBT), Keefektifan, Motif Tato Suku Dayak Iban, Perlindungan Hukum.